Surface modified MXene reinforced nylon composite material and preparation method thereof
By modifying the surface of MXene with amide bonds and imine bonds, the compatibility and uneven dispersion problems of MXene and nylon composites are solved, and the high performance of the composite materials is achieved. It is suitable for fields such as machinery, electronics, aerospace, automotive industry and high-performance electronic packaging.
Patent Information
- Application Number
- CN202510840022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-10-14
AI Technical Summary
In the existing technology, the composite of MXene and nylon has problems such as poor compatibility and uneven dispersion, which limits the performance improvement of the composite material.
MXene was surface-modified via amide and imine bonds, and combined with a compatibilizer, lubricant, antioxidant, and coupling agent, and surface-modified MXene-reinforced nylon composites were prepared by step-by-step addition and twin-screw extruder processing.
It improves the uniform dispersion and interfacial bonding strength of MXene in the nylon matrix, significantly enhances the mechanical properties, heat resistance and electromagnetic shielding properties of the composite material, and broadens the application areas of nylon materials.
Smart Images

Figure BDA0005461799330000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a surface-modified MXene-reinforced nylon composite material and a preparation method thereof. Background Art
[0002] Nylon (polyamide, PA) is a widely used engineering plastic with excellent mechanical properties, wear resistance, and chemical resistance. With the development of modern industry, higher requirements are placed on the performance of nylon materials, such as further improving its strength, modulus, and thermal stability.
[0003] MXene is a new class of two-dimensional inorganic materials characterized by a unique layered structure, high electrical conductivity, excellent thermal stability, and superior mechanical properties. Incorporating MXene into a nylon matrix holds promise for producing composite materials with superior overall performance. Currently, the primary method for preparing MXene is chemical etching. For example, the preparation of Ti3C2Tx from Ti3AlC2 involves adding Ti3AlC2 powder to a fluorine-containing compound, stirring the reaction at a constant temperature for several days, and then chemically etching the Al layer from the Ti3AlC2. The resulting product undergoes multiple centrifugation and washing steps, followed by freeze-drying to yield Ti3C2TxMXene. The very strong Ti-F and Ti-O bonds introduced during this process hinder subsequent surface group substitution. Consequently, the composites of MXene and nylon currently face challenges, such as poor compatibility and uneven dispersion of MXene in the nylon matrix, which limits the performance gains of the composites. Summary of the Invention
[0004] The object of the present invention is to provide a surface-modified MXene-reinforced nylon composite material and a preparation method thereof to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above objectives, in one aspect, the present invention provides the following technical solutions: a surface-modified MXene-reinforced nylon composite material, comprising the following components, by mass: 70 to 85 parts of nylon resin, 1 to 8 parts of amide bond and imine bond surface-modified MXene, 1 to 8 parts of a compatibilizer, 0.2 to 0.8 parts of a lubricant, 0.2 to 0.8 parts of an antioxidant, and 0.2 to 1.0 parts of a coupling agent;
[0006] The method for preparing MXene surface modified with amide bonds and imine bonds comprises the following steps:
[0007] S1: mixing Al-containing MAX phase powder and molten salt in a mass ratio of 1:5 to 1:10, placing the mixture in a closed reactor, heating the mixture to above the melting point of the molten salt under argon protection, and reacting the mixture at a constant temperature for 2 to 8 hours to obtain a molten salt etching product, wherein the Al-containing MAX phase powder is Ti3AlC2, and the molten salt is ZnCl2, CuCl2, or ZnBr2;
[0008] S2: The molten salt etching product is naturally cooled, washed with 1-3 M dilute hydrochloric acid or deionized water, immersed in deionized water, and treated with 20-40 kHz ultrasonic waves for 1-2 hours to obtain a MXene dispersion, which is then vacuum-dried at 60-80 °C to obtain a Cl / Br-terminated MXene powder;
[0009] S3: Cl / Br terminated MXene powder, primary organic amine and NaH are reacted at 120°C for 2d to obtain the amide bond and imine bond surface modified MXene, wherein the primary organic amine is one of alkylamine, diamine, aromatic amine and polyethylene glycol amine.
[0010] Optionally, the nylon resin is one or more of nylon 6, nylon 12, nylon 66, and nylon 1010.
[0011] Optionally, the compatibilizer is one or more of maleic anhydride grafted nylon, maleic anhydride grafted polyethylene, and maleic anhydride grafted POE.
[0012] Optionally, the lubricant is one or more of ethylene bisstearamide, ethylene-acrylic acid copolymer, erucamide, silicone powder, and stearate.
[0013] Optionally, the antioxidant is one or more of antioxidant 168, antioxidant 1010, antioxidant 1098, a mixture of phenolic antioxidants and phosphonates.
[0014] Optionally, the coupling agent is one or more of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-570.
[0015] On the one hand, the present invention also provides the following technical solution: a method for preparing a surface-modified MXene reinforced nylon composite material, comprising the following steps:
[0016] S1: First, nylon resin, compatibilizer, lubricant, antioxidant and coupling agent are added to a high-speed mixer, and then amide bond and imine bond surface modified MXene accounting for 20% to 40% of the total mass of amide bond and imine bond surface modified MXene is added to the high-speed mixer, and finally mixed at 100 to 150 ° C for 5 to 10 minutes to obtain a mixture;
[0017] S2: The mixture and the remaining amide bond and imine bond surface-modified MXene are added to a twin-screw extruder. The extruder temperature is set to 210-265°C and the screw speed is 320-350 rpm. Extrusion and granulation are performed to obtain the surface-modified MXene-reinforced nylon composite material.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention obtains amide- and imine-bonded surface-modified MXene by surface-modifying MXene, which facilitates the uniform dispersion of MXene in the nylon matrix and enhances the interfacial bonding between MXene and nylon resin, significantly improving the mechanical properties, heat resistance, and electromagnetic shielding properties of the composite material. In addition, the composite material has good thermal stability and can be used at higher temperatures, broadening the application field of nylon materials.
[0020] 2. The present invention reduces the local MXene concentration by step-by-step addition of amide and imine bond surface-modified MXene, avoiding agglomeration at high filling levels. The addition of amide and imine bond surface-modified MXene in a high-speed mixer can form a primary network in the nylon resin. The amide and imine bond surface-modified MXene introduced in a twin-screw extruder achieves further filling, increases the percolation threshold, and thus improves the mechanical and physical properties of the material. DETAILED DESCRIPTION
[0021] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0022] Example 1: The present invention provides a surface-modified MXene-reinforced nylon composite material, comprising the following components, by mass: 70 parts of nylon 6, 1 part of amide bond and imine bond surface-modified MXene, 1 part of maleic anhydride-grafted nylon, 0.2 parts of ethylene bisstearamide, 0.2 parts of antioxidant 168, and 0.2 parts of silane coupling agent KH-550;
[0023] The preparation method of MXene surface modified with amide bonds and imine bonds includes the following steps:
[0024] S1: Mix Al-containing MAX phase powder and molten salt in a mass ratio of 1:5, place the mixture in a closed reactor, heat it to above the melting point of the molten salt under argon protection, and react at a constant temperature for 2 hours to obtain a molten salt etching product, wherein the Al-containing MAX phase powder is Ti3AlC2 and the molten salt is ZnCl2;
[0025] S2: The molten salt etched product was naturally cooled, washed with deionized water, immersed in deionized water, and treated with 20 kHz ultrasonic waves for 1 h to obtain a MXene dispersion. The MXene dispersion was vacuum dried at 60 °C to obtain Cl-terminated MXene powder.
[0026] S3: Cl-terminated MXene powder, primary organic amine and NaH are reacted at 120 °C for 2 d to obtain amide bond and imine bond surface-modified MXene, wherein the primary organic amine is oleylamine.
[0027] The preparation method of the surface-modified MXene-reinforced nylon composite material comprises the following steps:
[0028] S1: First, nylon 6, maleic anhydride grafted nylon, ethylene bisstearamide, antioxidant 168, and silane coupling agent KH-550 were added to a high-speed mixer. Then, amide- and imine-modified MXene accounting for 20% of the total mass of amide- and imine-modified MXene was added to the high-speed mixer. Finally, the mixture was mixed at 100°C for 5 minutes to obtain a mixture.
[0029] S2: The mixture and the remaining amide- and imine-bond surface-modified MXene were added to a twin-screw extruder. The extruder temperature was set at 240°C and the screw speed was set at 350 rpm. Extrusion and pelletization were performed to obtain a surface-modified MXene-reinforced nylon composite material.
[0030] Example 2: The present invention provides a surface-modified MXene-reinforced nylon composite material, comprising the following components, by mass: 75 parts of nylon 12, 3 parts of amide bond and imine bond surface-modified MXene, 3 parts of maleic anhydride-grafted polyethylene, 0.4 parts of ethylene-acrylic acid copolymer, 0.4 parts of antioxidant 1010, and 0.5 parts of silane coupling agent KH-560;
[0031] The preparation method of MXene surface modified with amide bonds and imine bonds includes the following steps:
[0032] S1: Mix Al-containing MAX phase powder and molten salt in a mass ratio of 1:7, place the mixture in a closed reactor, heat it to above the melting point of the molten salt under argon protection, and react at a constant temperature for 4 hours to obtain a molten salt etching product, wherein the Al-containing MAX phase powder is Ti3AlC2 and the molten salt is CuCl2;
[0033] S2: The molten salt etched product was naturally cooled, washed with 1 M dilute hydrochloric acid, immersed in deionized water, and treated with 30 kHz ultrasonic waves for 1 h to obtain a MXene dispersion. The MXene dispersion was vacuum dried at 74 °C to obtain Cl-terminated MXene powder.
[0034] S3: Cl-terminated MXene powder, primary organic amine and NaH are reacted at 120 °C for 2 d to obtain amide bond and imine bond surface-modified MXene, wherein the primary organic amine is ethylenediamine.
[0035] The preparation method of the surface-modified MXene-reinforced nylon composite material comprises the following steps:
[0036] S1: Nylon 12, maleic anhydride grafted polyethylene, ethylene-acrylic acid copolymer, antioxidant 1010, and silane coupling agent KH-560 were first added to a high-speed mixer, and then amide- and imine-modified MXene (25% by weight of the total amide- and imine-modified MXene) was added to the high-speed mixer, and finally mixed at 120°C for 6 min to obtain a mixture;
[0037] S2: The mixture and the remaining amide- and imine-bond surface-modified MXene were added to a twin-screw extruder. The extruder temperature was set at 210°C and the screw speed was set at 330 rpm. Extrusion and pelletization were performed to obtain a surface-modified MXene-reinforced nylon composite material.
[0038] Example 3: The present invention provides a surface-modified MXene-reinforced nylon composite material, comprising the following components, by mass: 80 parts of nylon 66, 6 parts of amide bond and imine bond surface-modified MXene, 8 parts of maleic anhydride-grafted nylon, 0.6 parts of erucamide, 0.6 parts of antioxidant 1098, and 0.8 parts of silane coupling agent KH-570;
[0039] The preparation method of MXene surface modified with amide bonds and imine bonds includes the following steps:
[0040] S1: Mix Al-containing MAX phase powder and molten salt in a mass ratio of 1:8, place the mixture in a closed reactor, heat it to above the melting point of the molten salt under argon protection, and react at a constant temperature for 6 hours to obtain a molten salt etching product, wherein the Al-containing MAX phase powder is Ti3AlC2 and the molten salt is ZnBr2;
[0041] S2: The molten salt etched product was naturally cooled, washed with 2M dilute hydrochloric acid, immersed in deionized water, and treated with 35kHz ultrasonic waves for 1 hour to obtain a MXene dispersion. The MXene dispersion was vacuum dried at 75°C to obtain Br-terminated MXene powder.
[0042] S3: Br-terminated MXene powder, primary organic amine and NaH are reacted at 120 °C for 2 d to obtain amide bond and imine bond surface-modified MXene, wherein the primary organic amine is aniline.
[0043] The preparation method of the surface-modified MXene-reinforced nylon composite material comprises the following steps:
[0044] S1: Nylon 66, maleic anhydride grafted nylon, erucamide, antioxidant 1098, and silane coupling agent KH-570 were first added to a high-speed mixer, and then amide- and imine-modified MXene (35% by weight of the total amide- and imine-modified MXene) was added to the high-speed mixer, and finally mixed at 140°C for 8 minutes to obtain a mixture;
[0045] S2: The mixture and the remaining amide- and imine-bond surface-modified MXene were added to a twin-screw extruder. The extruder temperature was set at 265°C and the screw speed was set at 320 rpm. Extrusion and pelletization were performed to obtain a surface-modified MXene-reinforced nylon composite material.
[0046] Example 4: The present invention provides a surface-modified MXene-reinforced nylon composite material, comprising the following components, in parts by mass: 85 parts of nylon 1010, 8 parts of amide bond and imine bond surface-modified MXene, 5 parts of maleic anhydride-grafted POE, 0.8 parts of a mixture of silicone powder and stearate in a mass ratio of 1:1, 0.8 parts of a mixture of phenolic antioxidant and phosphonate, and 1.0 parts of a silane coupling agent KH-570;
[0047] The preparation method of MXene surface modified with amide bonds and imine bonds includes the following steps:
[0048] S1: Mix Al-containing MAX phase powder and molten salt in a mass ratio of 1:10, place in a closed reactor, heat to above the melting point of the molten salt under argon protection, and react at a constant temperature for 8 hours to obtain a molten salt etching product.
[0049] Among them, the Al-containing MAX phase powder is Ti3AlC2, and the molten salt is ZnBr2;
[0050] S2: The molten salt etched product is cooled naturally, washed with 3M dilute hydrochloric acid or deionized water, immersed in deionized water, and treated with 40kHz ultrasonic waves for 2h to obtain a MXene dispersion, which is then vacuum-dried at 80°C to obtain a Br-terminated MXene powder.
[0051] S3: Br-terminated MXene powder, primary organic amine and NaH are reacted at 120 °C for 2 d to obtain amide bond and imine bond surface-modified MXene, wherein the primary organic amine is polyethylene glycol amine.
[0052] The preparation method of the surface-modified MXene-reinforced nylon composite material comprises the following steps:
[0053] S1: Nylon 1010, maleic anhydride grafted POE, a mixture of silicone powder and stearate, a mixture of phenolic antioxidant and phosphonate, and silane coupling agent KH-570 were first added to a high-speed mixer, and then amide bond and imine bond surface modified MXene accounting for 40% of the total mass of amide bond and imine bond surface modified MXene was added to the high-speed mixer, and finally mixed at 150°C for 10 min to obtain a mixture;
[0054] S2: The mixture and the remaining amide- and imine-bond surface-modified MXene were added to a twin-screw extruder. The extruder temperature was set at 220°C and the screw speed was set at 350 rpm. Extrusion and pelletization were performed to obtain a surface-modified MXene-reinforced nylon composite material.
[0055] In Example 4, NaH was used as the deprotonating agent, and the overall reaction between Ti3C2Br2 and polyethylene glycol amine was as follows: PEG-NH2+NaH+Ti3C2Br2→Ti3C2(NR) x (NH-PEG) y +H2(g)↑+NaBr. The resulting amide bond and imine bond surface modified MXene is a MXene with amide bond and imine bond surface terminals as well as bare MXene.
[0056] Comparative Example 1
[0057] The method is basically the same as Example 1, except that the MXene surface is not modified using amide bonds and imine bonds.
[0058] Comparative Example 2
[0059] It is basically the same as Example 1, the only difference is that unmodified MXene is used to replace the amide bond and imine bond surface-modified MXene, and the unmodified MXene is Ti3C2Cl2.
[0060] Comparative Example 3
[0061] The method is basically the same as Example 1, except that the addition method of the amide bond and imine bond surface modified MXene is different. The preparation method of the surface modified MXene reinforced nylon composite material includes the following steps:
[0062] S1: add nylon resin, compatibilizer, lubricant, antioxidant and coupling agent into a high-speed mixer, mix at 100℃ for 5min to obtain a mixture;
[0063] S2: add the mixture and the MXene surface modified by amide bond and imine bond into a twin-screw extruder, set the temperature of the extruder to 240℃, and the screw rotation speed to 350rpm, extrude and pelletize to obtain the MXene surface modified nylon composite material.
[0064] Performance test
[0065] Test content: the material mechanical property test and the material physical property test are respectively carried out on examples 1-4 and comparative examples 1-3, and the test results are recorded in table 1.
[0066] Table 1
[0067]
[0068] As shown in table 1, by using the MXene surface modified by amide bond and imine bond, the MXene with amide bond and imine bond surface end and exposed MXene is successfully prepared, which significantly improves the dispersibility of MXene in the nylon matrix, so that it can be uniformly distributed in the polymer matrix, thereby avoiding the performance defects caused by agglomeration. At the same time, the interfacial bonding force between the modified MXene and the nylon resin is greatly improved, and the interaction between them is more closely and stably. Thanks to this optimized interface characteristics, the mechanical properties of the composite material are significantly enhanced, showing higher tensile strength, bending modulus and impact toughness; the heat resistance is also significantly improved, and the composite material can maintain stable physical properties at higher temperatures and is not prone to thermal degradation or deformation. In addition, the composite material also exhibits excellent electromagnetic shielding performance, which can effectively block the penetration of electromagnetic waves, and is suitable for electromagnetic interference protection of electronic equipment and other fields.
[0069] More importantly, the composite material also has good thermal stability, even in a higher temperature use environment, it can maintain the integrity of its structure and performance, thereby greatly widening the application range of nylon materials. This high-performance composite material is not only suitable for traditional mechanical and electronic fields, but also can be used in aerospace, automobile industry and high-performance electronic packaging and other extremely demanding high-end fields of material performance, providing new possibilities for the diversified application of nylon materials.
[0070] The method for surface modification of MXene by step-by-step addition of amide bond and imine bond can effectively reduce the problem of too high local concentration of MXene, especially under the condition of high filling amount, can significantly avoid the agglomeration phenomenon caused by too high concentration, first adding part of the amide bond and imine bond surface modified MXene in the high-speed mixer, can first build a primary network structure in the nylon resin, providing a uniform dispersion basis for the subsequent mixing process, continuously introducing the remaining amide bond and imine bond surface modified MXene in the twin-screw extruder, realizing further filling, not only filling the gap in the primary network, but also significantly improving the penetration threshold of the material, making the microstructure of the material more dense, and the interface interaction more sufficient, thereby significantly improving the mechanical properties and physical properties of the material.
[0071] Although embodiments of the present application have been shown and described, it is to be understood that various modifications, substitutions, replacements and changes can be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A surface-modified MXene-reinforced nylon composite material, characterized by: The following components are included by weight: 70-85 parts of nylon resin, 1-8 parts of amide bond and imine bond surface modified MXene, 1-8 parts of compatibilizer, 0.2-0.8 parts of lubricant, 0.2-0.8 parts of antioxidant, and 0.2-1.0 parts of coupling agent; The method for preparing MXene surface modified with amide bonds and imine bonds comprises the following steps: S1: mixing Al-containing MAX phase powder and molten salt in a mass ratio of 1:5 to 1:10, placing the mixture in a closed reactor, heating the mixture to above the melting point of the molten salt under argon protection, and reacting the mixture at a constant temperature for 2 to 8 hours to obtain a molten salt etching product, wherein the Al-containing MAX phase powder is Ti3AlC2, and the molten salt is ZnCl2, CuCl2, or ZnBr2; S2: The molten salt etching product is naturally cooled, washed with 1-3 M dilute hydrochloric acid or deionized water, immersed in deionized water, and treated with 20-40 kHz ultrasonic waves for 1-2 hours to obtain a MXene dispersion, which is then vacuum-dried at 60-80 °C to obtain a Cl / Br-terminated MXene powder; S3: Cl / Br terminated MXene powder, primary organic amine and NaH are reacted at 120°C for 2d to obtain the amide bond and imine bond surface modified MXene, wherein the primary organic amine is one of alkylamine, diamine, aromatic amine and polyethylene glycol amine.
2. The surface-modified MXene-reinforced nylon composite material according to claim 1, characterized in that: The nylon resin is one or more of nylon 6, nylon 12, nylon 66, and nylon 1010.
3. The surface-modified MXene-reinforced nylon composite material according to claim 1, characterized in that: The compatibilizer is one or more of maleic anhydride grafted nylon, maleic anhydride grafted polyethylene, and maleic anhydride grafted POE.
4. The surface-modified MXene-reinforced nylon composite material according to claim 1, characterized in that: The lubricant is one or more of ethylene bisstearamide, ethylene-acrylic acid copolymer, erucamide, silicone powder, and stearate.
5. The surface-modified MXene reinforced nylon composite material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 168, antioxidant 1010, antioxidant 1098, a mixture of phenolic antioxidants and phosphonates.
6. The surface-modified MXene-reinforced nylon composite material according to claim 1, characterized in that: The coupling agent is one or more of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-570.
7. A method for preparing a surface-modified MXene-reinforced nylon composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: First, nylon resin, compatibilizer, lubricant, antioxidant and coupling agent are added to a high-speed mixer, and then amide bond and imine bond surface modified MXene accounting for 20% to 40% of the total mass of amide bond and imine bond surface modified MXene is added to the high-speed mixer, and finally mixed at 100 to 150 ° C for 5 to 10 minutes to obtain a mixture; S2: The mixture and the remaining amide bond and imine bond surface-modified MXene are added to a twin-screw extruder. The extruder temperature is set to 210-265°C and the screw speed is 320-350 rpm. Extrusion and granulation are performed to obtain the surface-modified MXene-reinforced nylon composite material.
Citation Information
Cited By
Interface-enhanced rubber ring and electric smelting steel skeleton polyethylene composite pipe as well as preparation method and application of interface-enhanced rubber ring and electric smelting steel skeleton polyethylene composite pipe
CN122014926A